Implementation of First Time Electronic Land Registration by Notary as Officer of Land Deed Management at the Office of the National Land Agency - Vishnu Mareta Nugraha (Sultan Agung Notary Law Review, 2022)
This research aims to examine the Implementation of First Time Electronic Land Registration by Notary as Officer of Land Deed Management at the Office of the National Land Agency with the formulation of the problem, namely the stages in the implementation of electronic land registration certificates, the effectiveness of electronic certificates in the implementation of registration of certificates and solutions Electronic. The purpose of this research is to find out and analyze the stages in the implementation of Electronic Certificate land registration, the Effectiveness of Electronic Certificates and the Constraints and Solutions in the implementation of Electronic Certificate registration. The benefits and uses of this research are in the form of theoretical benefits and practical benefits, using normative research methods. Based on the research results, the procedure for issuing Electronic Certificates must refer to Government Regulation Number 24 of 1997 concerning land registration for land that has not been registered and does not have physical and juridical evidence in accordance with articles 11 and 12. Then to obtain an Electronic Certificate or replacement of an analogous Certificate becoming an Electronic certificate refers to the Regulation of the Minister of Spatial Planning of the Head of the National Land Agency Number 1 of 2021 concerning Electronic Certificates, namely Article 2, then the implementing regulations are issued, namely Government Regulation Number 18 of 2021 concerning management rights, land rights, apartment units and land registration that is article 84, furthermore the power of Electronic Certificates as authentic evidence of control of land rights is included in the expansion of documentary evidence, namely in Article 1866 of the Civil Code and certificates of land rights can be canceled for authenticity if they do not meet the elements of an authentic deed in accordance with the provisions of article 1868 civil law books and can subsequently be annulled if after 5 years of the issuance of a certificate there is an objection that they can file a lawsuit to the National Land Agency office or to the court in accordance with article 32 paragraph (2) Government Regulation Number 24 of 1997 concerning land registration.